PENERAPAN THRESHOLD DALAM PEMILU MENURUT PERSPEKTIF GUSTAV RADBRUCH DAN HANS KELSEN - Sholahuddin Al-Fatih (Universitas Muhammadiyah Malang, 2020)
This study tries to discuss the tensions that occur between legal experts in formulating basic values that become the right legal objectives. Figures that are used as a comparison in the perspective of this legal objective are Gustav Radbruch and Hans Kelsen. Through a conceptual and case approach, this study tries to examine the concept of law based on contextual cases that occur in society, namely the application of the threshold in elections. In this study, the application of the threshold in elections is used as a measuring tool to determine legal objectives as stated by Gustav Radbruch and Hans Kelsen. The results of this study indicate that Gustav Radbruch sees and tends to the value of justice as a legal goal, like what Hans Kelsen found. The difference between Gustav Radburch's justice and Hans Kelsen lies in how to measure and realize this justice. This research is expected to be able to help academics and legal practitioners to dig deeper into the philosophical objectives of law in order to create laws that can answer the needs of society.